PEMENUHAN KEBUTUHAN PANGAN BERAS PASCA PEMINDAHAN IBU KOTA NEGARA DI KABUPATEN PENAJAM PASER UTARA - Mursidah, Mursidah; Laily Ramadhan, M Rizky; Suriaatmaja, Muhammad Erwan (AGRIBIOS, 2025)
The relocation of Indonesia's capital city from Jakarta to East Kalimantan has various significant impacts, particularly on food supply, especially rice, in Penajam Paser Utara Regency. Rice is a strategic food commodity with high political, economic, and social value. This study aims were to analyzed the factors affecting rice availability and the impact of the capital relocation on rice food supply in Penajam Paser Utara Regency.The research was using a purposive sampling method to collect data from various sources, including the Central Bureau of Statistics and the Department of Agriculture of Penajam Paser Utara Regency. The data used includes population projections, land area, and rice production from 2019 to 2035. Simulations using a systems dynamics approach were conducted with Vensim software to predict rice availability and demand.The study indicated that the relocation of the capital city will lead to a significant population increase in Penajam Paser Utara Regency. The surge in population due to migration will lead to higher rice consumption, while land conversion will reduce the available area for rice production. Factors such as harvested area, productivity, and post-harvest efficiency also play a role in rice availability. It is projected that by 2025, there will be a deficit of 9,067 tons, with continued impact until 2035, where production will not be able to keep up with the increasing consumption. Without appropriate policy interventions to boost production through the development of agricultural infrastructure, farmer empowerment, and diversification of food sources, Penajam Paser Utara Regency is at risk of experiencing a food crisis, inflation that could threaten economic stability, and future food security.